Modernizing your Windows applications with the Windows app SDK and WinUI : expand your desktop apps to support new features and deliver an Integrated Windows 11 experience - Pagani, Matteo (Packt Publishing, Limited, 2022)
Use Windows App SDK and WinUI 3 to take your existing Windows desktop applications to the next level by enabling a modern and accessible UI and integrating the latest Windows features like WinML and Windows Hello Key Features Improve your apps and enable them to support modern devices with features such as touch screens and responsive UI Integrate your app with the latest Windows innovations using modern tools and the newest C# features Reuse your existing knowledge in .NET, C#, and Visual Studio to create new Windows apps Book Description If you're a developer looking to improve and modernize your existing LOB applications to leverage modern Windows features without having to rewrite the entire application from scratch, this book is for you. You'll learn how to modernize your existing Windows Forms, WPF, and UWP applications and enrich them with the latest Windows features. Starting with sample LOB applications that cover common scenarios, you'll learn the differences between various components and then focus on design features for improved visual aspects like accessibility and responsive layouts. The book shows you how to enhance your existing applications using Windows App SDK components and various Windows APIs, resulting in deeper integration with the operating system. You'll be taking a closer look at WinML, which enables Windows applications to evaluate machine learning models offline and leverage the power of your machine, or notifications, to engage with your users in a more effective way. You'll also learn how to make your application deployment-ready by distributing it using various platforms like the Microsoft Store or websites. By the end of this Windows book, you'll be able to create a migration plan for your existing Windows applications and put your knowledge to work by enhancing your application with new features and integrating them with the Windows ecosystem. What you will learn Understand the key concepts of the Windows App SDK and WinUI Integrate new features by creating new applications or by enhancing your existing ones Revamp your app's UI by adopting Fluent Design and new interaction paradigms such as touch and inking Use notifications to engage with your users more effectively Integrate your app with the Windows ecosystem using the Windows App SDK Use WinML to boost your tasks using artificial intelligence Deploy your application in LOB and customer-facing scenarios with MSIX Who this book is for This book is for developers who are building Windows applications with Windows Forms, WPF, and UWP and would like to evolve and modernize their applications, but aren't able to rebuild them from scratch. This book focuses on Line-of-Business scenarios. Basic knowledge of Windows app development, .NET/C#, and Visual Studio will help you understand the concepts covered in this book.